Perencanaan Pembelajaran PAI Berbasis Blended Learning: Studi Pada Sekolah Menengah Atas di Era Pasca Pandemi - Azka Azkiya; Zuyina Huda; Mar’atul Izwah; Akhdan Nurrahman; Dodi Ardiayansyah (Penerbit Minhaj Pustaka, 2026)
In the early days of Covid-19, Learning in the world of Education Indonesia switched to online learning with some Obstacles felt by students and teachers, so that Learning is carried out again with face-to-face learning. Face, so that for the first time using the blended learning model in learning. Based on that, this research examines in depth about